2014
DOI: 10.1080/01635581.2015.965335
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Inhibition of CYP1A1 and Glutathione S-Transferase Activities in Fish Liver by Quercetin, Resveratrol, Naringenin, Hesperidin, and Rutin

Abstract: Quercetin, resveratrol, naringenin, hesperidin, and rutin are phenolic compounds/flavonoids that may have roles in the reduction of cancer susceptibility. In this study, in vitro modulatory effects of them were studied on liver CYP1A1 associated 7-ethoxyresorufin-O-deethylase (EROD) activity and glutathione S-transferase (GST) activity of leaping mullet (Liza saliens). All of the phenolic compounds/flavonoids used exerted an inhibitory effect on both EROD and GST activities of fish. Quercetin, resveratrol, hes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 55 publications
0
15
0
Order By: Relevance
“…Rutin, a pharmaceutically and medicinally valuable compound, existed in methanol and water extracts of both plant species. Recent work about the rutin indicated that it has antioxidant (Das et al 2015), antibacterial (Ananth et al 2015), antidiabetic (Wang et al 2015), anticancer (Arinc et al 2015), antiepileptic (Dubey et al 2015), antimalarial (Choudhary et al 2014) and antithyroid (Panda and Kar 2014) properties. The water extract of E. purpurea leaves, E. purpurea flowers, E. pallida leaves and E. pallida flowers revealed the excellent ABTS cation radical (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Rutin, a pharmaceutically and medicinally valuable compound, existed in methanol and water extracts of both plant species. Recent work about the rutin indicated that it has antioxidant (Das et al 2015), antibacterial (Ananth et al 2015), antidiabetic (Wang et al 2015), anticancer (Arinc et al 2015), antiepileptic (Dubey et al 2015), antimalarial (Choudhary et al 2014) and antithyroid (Panda and Kar 2014) properties. The water extract of E. purpurea leaves, E. purpurea flowers, E. pallida leaves and E. pallida flowers revealed the excellent ABTS cation radical (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…40 Hesperidin and rutin are vast and ranging in its ability to inhibit liver enzymes due to their antithyroid effects. 41,42 It has also been shown to possess anti-inflammatoty, antioxidant, hypolipaedemic and anti-carcinogenic activities. 43 Pipentol is a known flavouring agent which are commoly used in fragrance chemistry.…”
Section: Discussionmentioning
confidence: 99%
“…Fold-inhibition was calculated using the following formula: 2 -∆∆Ct , where ∆∆Ct=∆Ct(treated)−∆Ct(control); ∆Ct(treated)=∆Ct(CY Ps)−∆Ct(GAPDH); ∆Ct(control)=∆Ct(CYPs)−∆Ct(GAPDH). especially by preventing the induction of CYP1A isozymes [42,43]. In light of the role of CYP1A in the formation of reactive products, the observed inhibition of CYP1A mRNA expression by the SF extract and its major phenolic component vanillic acid could lead to the reduction or prevention of the onset of many diseases, including cancer.…”
Section: Discussionmentioning
confidence: 99%